Evaluation of Diagnostic Accuracy of Percutaneous Biopsy for Small Renal Masses and First Report of Post-Biopsy Adhesions: A Prospective Study - Doganca, Tunkut; Obek, Can (Urology Journal, 2019)
Purpose: In the present study, we evaluate the biopsy results, complications due to biopsy, and the correlation with the final pathology specimen of 19 patients who had surgery for their small renal masses. Materials and Methods: A total of 19 patients (11 male, 8 female) underwent percutaneous biopsy of their renal mass under ultrasound guidance. All patients subsequently underwent extirpative surgery. Preoperative biopsy results were compared with postoperative specimens in terms of tru-cut and fine needle aspiration biopsies’ histopathological accuracy and the complications noted. Results: Average age was 56(±10.5) and tumor size was 37(±10.6) mm. Six patients had only fine needle, 4 patients had only tru-cut, and 9 patients had both fine needle and tru-cut biopsies. Malignancy was reported in 14, and benign results in 5 patients. Sensitivity, specificity, PPV and NPV’s were 64%, 100%, 100%, 33% respectively for FNAB. Sensitivity, specificity, PPV and NPV’s were all 100% for tru-cut core biopsy. Two perirenal hematoma was detected which resolved spontaneously under conservative therapy. In 11 patients there were adhesions due to biopsy, which caused difficulty of dissection during the operation. Conclusion: In this relatively small serie, percutenous ultrasound guided biopsy to determine the histology of small renal masses achieved a high diagnostic accuracy. FNAB alone has a low diagnostic accuracy with false negative results when compared. However, tru-cut core biopsy has a diagnostic accuracy of %100. Therefore we recommend tru-cut biopsy when histopathological diagnosis is required for small renal masses. Adhesions due to biopsy may cause difficulties during dissection.